Deciphering mechanisms of nonhost resistance against Zymoseptoria Tritici in model plant species - IGNA, ALINA-ANDRADA (2024)
The fungus Zymoseptoria tritici, causal agent of Septoria tritici blotch (STB) disease of wheat, poses a significant economic threat to all major temperate rainfall wheat-growing regions over the world owing to yield losses and the high cost of chemical disease control. Whilst the molecular nature of Z. tritici virulence toward its natural host (wheat) has been thoroughly studied, the mechanisms of nonhost resistance (NHR) to Z. tritici have only recently garnered attention. In a previous published study, Nicotiana benthamiana was used to investigate NHR to Z. tritici. Cell death triggered by specific effectors was found to be dependent on BAK1 - well-known coreceptor for many plant Cell Surface Immune Receptors (CSIRs). Thereby, it is hypothesised that recognition of Z. tritici effectors in N. benthamiana is governed by BAK1-dependent CSIRs. The PhD project aimed at identifying N. benthamiana BAK1-dependent putative CSIRs recognising the corresponding Z. tritici effectors, by leveraging a proteomics approach that uses BAK1 as molecular bait. However, the results unexpectedly revealed a candidate CSIR for an experimental control – the apoplastic effector Cell Death-Protein 1 of a pine wood nematode. Further investigations within this study delved into the kinetics of MAPKs. The results revealed that the transient expression of Z. tritici effectors in N. benthamiana leads to MAPKs activation prior to cell death, suggesting a role of MAPKs as part of the NHR response. Additionally, this research explored the production of purified Z. tritici effector proteins. However, following syringe infiltration of protein preps into N. benthamiana leaves failed to trigger an anticipated cell death response. To gain further insight into the NHR mechanism, I conducted preliminary experiments in various N. benthamiana mutant lines, with a particular focus on major ETI components required for signalling cascade responsible for cell death triggered by various CSIRs. Initial observations suggest that EDS1 and SA might contribute to the induction of cell death observed in N. benthamiana leaves following transient expression of specific Z. tritici effectors.